mTOR Inhibitors in the complex treatment of high-risk vascular malformations in children - I.M. Benzar; D.V. Zhumik (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2020)
Recent experimental and clinical studies demonstrated that mTOR receptor inhibitors can stop the progression of vascular malformations and significantly improve patients' quality of life. This is possible due to the interruption of the chain of phosphatidylinositol-3-kinase (PI3K) / AKT / mTOR reactions. The purpose of the study is to assess the efficacy and safety of mTOR receptor inhibitors in children with high-risk vascular malformations. Materials and methods. Six patients, from 1 to 9 years old, with extensive lymphatic malformations (n=3), complex slow-flow malformations - kaposiform lymphangiomatosis (n=1), Gorham-Stout disease (n=1), Klippel-Trenaunay syndrome (n=1), refractory to standard care, were enrolled in this study. Sirolimus was administered orally at initial dosage of 0.8 mg/m2/12 hour with pharmacokinetic-guided target serum concentration level of 5 to 10 ng/ml. The primary endpoints were safety and efficacy, based on clinical, laboratory and radiological evaluations. Results. The duration of sirolimus treatment was from 6 to 24 months. All patients had improvement in one or more aspects of their diseases. It was relief of respiratory symptoms, stop of pleural effusion, normalization of blood coagulation parameters, discontinuation of bleeding and lymphorrhea, pain relief and as a result quality of life improvement. Radiological signs of treatment efficiency were reduction of the lesion size and stopping of the osteolysis. Sirolimus was well tolerated, with leucopenia (n=1), stomatitis (n=2), and dyslipidemia (n=2) adverse event. In no case was complete recovery of the patient observed, but there was no deterioration in the course of the disease. Conclusions. Sirolimus was efficient in extensive LM and complex vascular malformations that were refractory to conventional treatments and was well tolerated. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of all participating institution. The informed consent of the patient was obtained for conducting the studies.